Familial Ankyloglossia (Tongue-tie): A Case Report - Saeid Morowati; Mobin Yasini2; Reza Ranjbar; Ali Asghar Peivandi; Mohsen Ghadami (Acta Medica Iranica, 2010)
Ankyloglossia (tongue-tie) is a congenital anomaly with a prevalence of 4-5% and characterized by an abnormally short lingual frenulum. For unknown reasons the abnormality seems to be more common in males. The pathogenesis of ankyloglossia is not known. The authors report a family with isolated ankyloglossia inherited as an autosomal dominant or recessive trait. The identification of the defective gene(s) in these patients might reveal novel information on the pathogenesis of this disorder.